Community-led Economic Resilience: Fostering SME Growth through Financial Education - Sutomo, Deni Anggreani (Manunggal Halim Jaya, 2024)
This study investigates the role of financial education in fostering small and medium-sized enterprise (SME) growth and resilience within the context of community-led economic resilience. The research aims to explore the determinants of SME resilience, the influence of community-led financial education interventions on SME performance, and the factors shaping the effectiveness of these initiatives. A qualitative literature review methodology is employed, involving systematic data collection from academic databases, journals, and other relevant sources. Qualitative data analysis techniques, including thematic analysis and content analysis, are utilized to extract key insights and develop coherent narratives from the literature. The findings highlight the pivotal role of financial education in enhancing SME performance, resilience, and sustainability, with empirical evidence supporting the positive correlation between financial literacy and various indicators of SME success. Moreover, community-led approaches to economic resilience are underscored as effective strategies for promoting sustainable development and mitigating vulnerabilities within local communities. The integration of social and human capital perspectives enriches the understanding of community-led economic resilience and SME development, emphasizing the importance of tailored interventions and collaborative partnerships. The study contributes to advancing knowledge and understanding in the field, providing valuable insights for policymakers, practitioners, and researchers alike.